2014
DOI: 10.1039/c3dt52654b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular tectonics: anion control of dimensionality and connectivity in meta-pyridyl appended tetramercaptotetrathiacalix[4]arene based silver coordination networks

Abstract: The combination of the same organic tecton 1, a meta-pyridyl appended tetramercaptotetrathiacalix[4]arene in 1,3-alternate conformation offering four pyridyl units and eight thioether groups, with three silver salts AgX (X = BF4(-), NO3(-) and SbF6(-)) leads, under identical conditions (concentration, temperature and solvent system), to the formation of different silver coordination networks. Both the connectivity and the dimensionality of the three silver coordination networks depend on the nature of the anio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…The geometry of the final self-assembly was determined by both structural and coordination features of the organic tecton. The authors suggested that the obtained perspective molecular architectures can be used in catalysis, optics, electronics and magnetism [73][74][75][76][77][78][79][80][81][82].…”
Section: Self-assembly Of Thiacalix[4]arenes With Ag(i) Ionsmentioning
confidence: 99%
“…The geometry of the final self-assembly was determined by both structural and coordination features of the organic tecton. The authors suggested that the obtained perspective molecular architectures can be used in catalysis, optics, electronics and magnetism [73][74][75][76][77][78][79][80][81][82].…”
Section: Self-assembly Of Thiacalix[4]arenes With Ag(i) Ionsmentioning
confidence: 99%
“…However, for both TCA and TMTCA, the presence of bridging S atoms not only leads to an enhancement of the size of the macrocycle cavity but also provides additional coordinating sites. Tetrasubstituted thiacalix[4]arene derivatives bearing cyano, [17][18][19] carboxyl, [20][21][22] pyridyl, [23][24][25][26][27][28] coordinating groups were combined with metal cations for the formation of coordination networks displaying a variety of dimensionalities (1D-3D). In contrast to CA, for these sulfur containing tectons, only the 1,3-alternate conformation has been used.…”
Section: молекулярная тектоника: 1d тубулярная структура и 3d алмазопmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that the dimensionality of the resulting network may be controlled either by the localization of the N atoms or by the nature of the counter ions. [23,27] Here, we report on the preparation of two new coordination networks obtained by combining pyridyl TCA Pyridyl TCA based tectons 3, 4, 5. [23] derivatives in 1,3-alternate conformation 4 (N atom of the pyridyl in meta position) and 5 (N atom of the pyridyl in para position) ( Figure 2) with HgCl 2 , acting as V-shape twoconnecting metallatecton.…”
Section: молекулярная тектоника: 1d тубулярная структура и 3d алмазопmentioning
confidence: 99%
“…1. The same weak noncovalent interactions have to be considered together with curvature and packing in molecular tectonics [29,30]. The influence of "weaker" forces triggers the formation of weaker thermodynamically stable structured aggregates, which will be the topic of next special issue of current opinion, to appear in 2016.…”
mentioning
confidence: 99%